FORMULATION AND ANTIBACTERIAL TEST OF STAR ANISE EXTRACT (Illicium verum Hook.F) AS A HAND SANITIZER - Dhanang Puspita; Eli Ardhiawati; Desi Desi (Universitas Medan Area, 2020)
The hand becomes one of the body parts that are easily exposed to microorganisms because of their high mobility. Hand sanitizer is a liquid that can be used to kill microbes. Hands become one of the body parts that are easily exposed to microorganisms because of their high mobility. Hand sanitizer is a liquid that can be used to kill microorganisms. Most hand sanitizers contain alcohol and triclosan, which can be bad for the skin if used in excessive amounts. It is necessary to substitute alcohol and triclosan as an antibacterial, one of which is star anise (Illicium verum Hook.f). Star anise contains flavonoids and tannins, which can function as antibacterial and safe for health. The objective of this study was to make a hand sanitizer formulation from star anise and test its antibacterial strength. The method used was a laboratory experiment with stages; Star anise extraction and antibacterial test. The results of the hand sanitizer formulation of the biggest star anise extract in inhibiting are 10% star anise extract. Inhibitory zone of 10% star anise extract at 6.2 ± 0.76 mm and included in the medium category.